Actions of primary health care professionals to reduce maternal mortality in the Brazilian Northeast - Katia M. S. Figueiredo; Gleice A. A. Gonçalves; Hermes M. T. Batista; Marco Akerman; Woneska R. Pinheiro; Vânia B. Nascimento (BMC, 2018)
Abstract Background Maternal mortality is a global public health problem. Statistics show that in 2013, 289,000 women died from complications during pregnancy, childbirth or the postpartum period worldwide. Between 2010 and 2015, there were 10,075 maternal deaths in Brazil, 3,522of which occurred in the Northeast region. The aim of this study was to investigate the actions taken by primary health care (PHC) professionals to reduce maternal mortality. Method This was a cross-sectional, descriptive field study with a qualitative approach. The sample comprised 81 graduate-level professionals working in PHC in the state of Ceará, Brazil. Data were collected from January to March 2016 using structured interviews, which were digitally audio recorded and transcribed. The results were organized using collective subject discourse and analyzed according with the relevant literature. Results The PHC professionals took both individual and joint measures to reduce maternal mortality. These activities included home visits, health education, active searches, prenatal care consultations, referrals to specialized care and outreach. The challenges that must be overcome to prevent maternal mortality include poor care and ineffective public policies that are associated with a lack of managerial support. Conclusion Interaction among professionals in the health care network is critical to the development of cross-sectoral projects that improve the quality of women's health care. Prenatal care is a key factor in reducing maternal death and enables the identification and classification of the risks to which pregnant women may be exposed and the implementation of early actions that can ensure a safe and uncomplicated delivery. However, all of these actions require effective public policies and managerial support.